Recent Trends in the Historiography of Iran under the Pahlavi Dynasty, 1921–1979 - Schayegh, Cyrus (History compass, 2008)
This article has two aims. It outlines the historiography of Pahlavi Iran, maintaining that historians have often written about this period from the perspective of the state. It also examines a small number of recent texts that have been instrumental in shifting the historiographic focus on the Pahlavi period: they are complicating our often monolithic view of ‘the state’ as well as its interactions with social groups.